Professional experiences of on-call specialists in the field of violations of children’s rights - Daiva Malinauskienė; Aistė Igorytė (Social Welfare: Interdisciplinary Approach)
The article analyses the content of the activity of child rights protection on-call specialists, their experiences related to the representation of the child and his/her interests. In Lithuania, this position is new and it emerged after the reform of the child rights protection system, which was caused by the increase in cases of violence against children, which resulted in their death several times. The activity of on-call specialists is focused on making quick decisions in response to reports of violations of children’s rights in the family and society.